Dynamic Wildlife Photography : Techniques for Creating Captivating Images - Illg, Cathy and Illg, Gordon (Buffalo, NY Amherst Media, 2004)
Learn to create meaningful, dynamic wildlife images that go beyond documentary photography. Today's viewers of wildlife photography are extremely savvy; they've seen thousands of photos from around the world, so it takes a lot to impress them. As a result, today's wildlife photographers also need to be very sophisticated to succeed. In this book, Cathy and Gordon Illg show you how to rise to this challenge, creating images that are truly dramatic and unique. For experienced photographers who want to apply their technical skills to wildlife photography and for photographers who already have experience with photographing animals but want to further refine their images, this book provides the guidance needed to master artistically compelling wildlife portraits. Photographers learn how to create images that not only document their subjects, but also cause viewers to study and discuss them. Written for photographers who know how to create a technically precise photograph, this book shows them how to flex their creativity, apply their imaging prowess to the field, and evaluate their subjects in a new light. Practical tips cover everything from backlighting the soft, downy "stubble" of a newborn chick to choosing and using the accessories that help capture a unique perspective. The book features, understanding what qualities set dynamic wildlife images apart from those that merely document the subject, how to decide what animals to photograph, from those that you see every day to exotic species from around the world, composition techniques for more effective wildlife images, including ideas for subject placement, framing, and working with cluttered backgrounds, determining the best way to present your subject, from wide-angle images that show the environment, to close-ups that isolate the animal in the frame, making the most of the light on your subject, whether it?s front light, side light, or even back light, identifying the qualities of your subjects that make them truly special, and capturing these in your images, celebrating the seasons with images that reflect animals in wintery landscaped, autumn foliage, and more
include Illustrations, Appendix and Index
Keywords: Wildlife photography